Ottoman Çiftlik/Zemin holdings in the grounds of ancient Salona and the Ager Salonitanus before the Fall of Klis (1537) - Ursinus, Michael (Tusculum, 2020)
The survey register TD 157 (tahrir defter) is the earliest Ottoman survey register to throw some light on the gradual incorporation into the Sultan’s realm of the territories situated in the immediate vicinity of Klis. As is well...